Pengaruh penambahan tepung daun Ciplukan (Physalis angulata L) yang difermentasi dengan Em4 pada pakan untuk pertumbuhan dan kelangsungan hidup ikan Nila (Oreochromis nilotius) - Rustiana Widaryati (Fakultas Peternakan Universitas Kristen Palangka Raya, 2019)
The purpose of this study was to determine the Effect of addition of Ciplukan (Physalis angulata L) flour fermented with EM 4 in feed to increase the growth of Nile Tilapia (Oreochromis niloticus). Treatments given A 0.5 gr / ml, B 1 gr / ml, C 1.5 gr / ml. Observation parameters were absolute growth, feed conversion and survival. The results of the study showed that giving Ciplukan flour fermented with probiotics in commercial feed had a very significant influence on absolute growth and survival of Nile Tilapia. The best dose of 1 gr / ml (treatment B) gave the highest growth of 1.7 followed by treatment A (0.5 gr / ml) of 0.8 and the lowest in treatment C (1.5 gr / ml) was 0.5. Keywords : Ciplukan (Physalis angulata L), EM 4 (Effective Microorganism 4), Nile Tilapia